2006
DOI: 10.1109/tbme.2006.881783
|View full text |Cite
|
Sign up to set email alerts
|

A New Decoupling Method for Quadrature Coils in Magnetic Resonance Imaging

Abstract: A powerful decoupling method is introduced to obtain decoupled signal voltages from quadrature coils in magnetic resonance imaging (MRI). The new method uses the knowledge of the position of the signal source in MRI, the active slice, to define a new mutual impedance which accurately quantifies the coupling voltages and enables them to be removed almost completely. Results show that by using the new decoupling method, the percentage errors in the decoupled voltages are of the order of 10(-7) % and isolations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In addition to theoretical studies, we have recently demonstrated experimentally that the RMIM can be used for mutual coupling compensation [28]. The RMIM has also been applied to mutual coupling compensation of DOA estimations using circular array [29] and phase array in Magnetic Resonance Imaging (MRI) [30][31][32]. Recently, the RMI has been adopted to model the mutual coupling effect of Multiple-Input Multiple-Output (MIMO) system and new models for channel capacities of the MIMO systems have been developed [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to theoretical studies, we have recently demonstrated experimentally that the RMIM can be used for mutual coupling compensation [28]. The RMIM has also been applied to mutual coupling compensation of DOA estimations using circular array [29] and phase array in Magnetic Resonance Imaging (MRI) [30][31][32]. Recently, the RMI has been adopted to model the mutual coupling effect of Multiple-Input Multiple-Output (MIMO) system and new models for channel capacities of the MIMO systems have been developed [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Hence the position information of the active slice is available and can be used to define the receiving mutual impedance for MRI phased arrays in a very accurate manner. Studies using this method to decouple the array signals have been found in MRI surface coil arrays and MRI quadrature coils [23][24]. It was shown that mutual coupling could be almost totally removed and nearly coupling-free array signals can be obtained.…”
Section: Receiving Mutual Impedance Methodsmentioning
confidence: 99%
“…The receiving mutual impedance (RMI) has been used for decoupling in adaptive nulling [15] and direction finding [13] applications, resulted in better estimation accuracies comparing to the case when conventional mutual impedance is used for decoupling. The RMIM has also been applied to near-field imaging application such as magnetic resonance imaging [18].…”
Section: 0 >mentioning
confidence: 99%